STUDI TERHADAP THEOLOGI KATOLIK DAN PROTESTAN - Abu Bakar (Lembaga penelitian dan pengabdian kepada masyrakat, 2012)
Confidence that Paulus as Christ proxy and can give its people sin pardon and is the understanding of past of boundary, hence Martin Luther protest to Pope and The Roman Catholic of Roma. As a result delivering birth different sect with Roman religion, recognized with the title Church Protestant. Of the problem hence in Christian religion recognized with two big stream which recognized till now, namely Christian Roman and Protestant